IRF8 regulates efficacy of therapeutic anti‐CD20 monoclonal antibodies. Issue 10 (7th September 2022) - Grzelak, Ludivine; Roesch, Ferdinand; Vaysse, Amaury; Biton, Anne; Legendre, Rachel; Porrot, Françoise; Commère, Pierre‐Henri; Planchais, Cyril; Mouquet, Hugo; Vignuzzi, Marco; Bruel, Timothée; Schwartz, Olivier
Abstract: Anti‐CD20 monoclonal antibodies such as Rituximab, Ofatumumab, and Obinutuzumab are widely used to treat lymphomas and autoimmune diseases. They act by depleting B cells, mainly through Fc‐dependent effectors functions. Some patients develop resistance to treatment but the underlying mechanisms are poorly understood. Here, we performed a genome‐wide CRISPR/Cas9 screen to identify genes regulating the efficacy of anti‐CD20 antibodies. We used as a model the killing of RAJI B cells by Rituximab through complement‐dependent‐cytotoxicity (CDC). As expected, the screen identified MS4A1, encoding CD20, the target of Rituximab. Among other identified genes, the role of Interferon Regulatory Factor 8 (IRF8) was validated in two B‐cell lines. IRF8 KO also decreased the efficacy of antibody‐dependent cellular cytotoxicity and phagocytosis (ADCC and ADCP) induced by anti‐CD20 antibodies. We further show that IRF8 is necessary for efficient CD20 transcription. Levels of IRF8 and CD20 RNA or proteins correlated in normal B cells and in hundreds of malignant B cells. Therefore, IRF8 regulates CD20 expression and controls the depleting capacity of anti‐CD20 antibodies. Our results bring novel insights into the pathways underlying resistance to CD20‐targeting immunotherapies. Abstract : In B cells, IRF8 protein induces MS4A1 transcription which encodes CD20 protein. CD20 is recognized by anti‐CD20 antibodies such as Rituximab, Ofatumumab and Obinutuzumab. Complement‐dependent cytotoxicity (CDC), Antibody‐Dependent Cell Cytotoxicity (ADCC) and Antibody‐Dependent Cellular Phagocytosis (ADCP) are then induced. Knocking‐out of IRF8 reduces CD20 levels and sensitivity to anti‐CD20 antibodies.